2011
DOI: 10.1073/pnas.1100735108
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 2 modulates endoplasmic reticulum (ER)–mitochondria interactions and Ca 2+ cross-talk

Abstract: Presenilin mutations are the main cause of familial Alzheimer's disease (FAD). Presenilins also play a key role in Ca 2+ homeostasis, and their FAD-linked mutants affect cellular Ca 2+ handling in several ways. We previously have demonstrated that FAD-linked presenilin 2 (PS2) mutants decrease the Ca 2+ content of the endoplasmic reticulum (ER) by inhibiting sarcoendoplasmic reticulum Ca 2+ -ATPase (SERCA) activity and increasing ER Ca 2+ leak. Here we focus on the effect of presenilins on mitochondrial Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
288
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(316 citation statements)
references
References 31 publications
22
288
4
2
Order By: Relevance
“…HGP, hepatic glucose production; IR, insulin receptor. (3,(31)(32)(33). Using this method to evaluate ER-mitochondria interactions, we found that MAM integrity is required for efficient insulin action in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…HGP, hepatic glucose production; IR, insulin receptor. (3,(31)(32)(33). Using this method to evaluate ER-mitochondria interactions, we found that MAM integrity is required for efficient insulin action in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ER-mitochondrial contacts are increased and ER-mitochondrial crosstalk is enhanced in PSEN1 knockout cells, in cells overexpressing the FAD mutant PSEN2, and in fibroblasts from FAD and sporadic AD patients (Zampese et al 2011;Area-Gomez et al 2012;Kipanyula et al 2012). Thus, PSENs are critically positioned where ER and mitochondria communicate and share contents (e.g., calcium, lipids, ATP).…”
Section: Discussionmentioning
confidence: 99%
“…MEFs (WT, Mfn2 −/− ) were grown as previously described (18), as were SH-SY5Y and HeLa cells (22). All materials were from Sigma-Aldrich unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…Aequorin measurements were carried out as described (22) and are summarized in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation